El trabajo cooperativo para el desarrollo de la destreza lógico matemática en los estudiantes de preparatoria de la escuela de educación básica “José Ingenieros”, del Recinto el Caimito, cantón Baba, provincia de los Ríos, año lectivo 2018 - 2019 - Díaz Tapia, Mercedes (2019)
The objective of this research work was to strengthen cooperative work as a didactic strategy for the development of skills in the field of mathematical logic relations. The methodology used in this research was qualitative, descriptive, a field and bibliographic-documentary modality, it has a research-action design of the Educational Sciences, of longitudinal cut, evaluating 12 students of the initial level through the Basic Skills Test for Introduction to Calculus (TIC), in charge of identifying the skills developed in mathematical areas. A playful guide of mathematical logic activities was applied. Finally, the alternative hypothesis was accepted where the cooperative work SI strengthens the development of mathematical logic skills in